ANALYSIS OF THE ROLE OF THE CIREBON CITY DPRD IN THE PREPARATION AND SUPERVISION OF LOCAL REGULATIONS FOR PUBLIC SERVICES - Harmono Harmono; Barlian Mahia Nurwahyu; Fani Zahara Suwarno Putri; Indra Pratama Putra (Jurnal Abdisci, 2025)
Abstract Background. The Regional People's Representative Council (DPRD) plays a strategic role in preparing and supervising Regional Regulations (Perda) to improve the quality of public services. Aims. This study analyzes the role of the Cirebon City DPRD in the legislative process and supervision of Regional Regulations and identifies the obstacles faced. Methods. Data is obtained from official documents such as Regional Regulation Number 5 of 2020 using a descriptive qualitative method. Result. The study's results show that the DPRD performs its functions through the Regional Regulation Formation Program (Propemda), recess, and policy evaluation. Conclusion. However, obstacles such as a lack of synchronization with executives, academic studies, and low public participation are still challenges. Implementation. Therefore, it is necessary to increase collaboration with academics and NGOs, strengthen the supervisory function, and optimize digital technology in legislation and socialization of regional regulations.